Pattern of ocular trauma in tertiary care hospital in Khammam - Nagrale, Prachee; Kesuraju, Vijaykumar; MR, Madhavi; Harsora, Vimal (International Journal of Research in Medical Sciences, 2017)
Background: Ocular trauma is an important public health hazard. The objective of the study was to determine the pattern of ocular trauma among patients presenting in Mamata Medical College and Hospital, Khammam. Methods: Two years retrospective review of records of 120 patients with ocular trauma seen from Jan 2013 to Feb 2015 was done using a structured format. Results: Ocular trauma accounted for 1.2% of the total ocular patients seen at OPD and Emergency. Of the studied 120 cases, 74 patients were below 30 years of age. 17 (14.16%) patients presented to hospital within 2-7 days of injury. Conclusion: Duration of presentation has significant association with the presence of infection & other complication. The cause of injury were road traffic accidents, occupation related and sports playing & recreational activities in 54(45%), 39(32.5%) and 24(20%) respectively. Closed globe injuries accounted for 38(31.66%) and open globe for 58(48.33%) and adenexal injuries constituted 24(20%). Delay in presentation was associated with complications.